2020
DOI: 10.1016/s2468-1253(19)30320-6
|View full text |Cite
|
Sign up to set email alerts
|

Safety of two different doses of simvastatin plus rifaximin in decompensated cirrhosis (LIVERHOPE-SAFETY): a randomised, double-blind, placebo-controlled, phase 2 trial

Abstract: Grant support and Acknowledgements: This work has been supported by funding from EU H2020 Research & Innovation programme, No. 731875 (LIVERHOPE).We acknowledge Nicola Van Berckel for her administrative support and her valuable collaboration with the development of the Liverhope Project.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
78
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 107 publications
(80 citation statements)
references
References 27 publications
0
78
0
2
Order By: Relevance
“…Several additional steps in simvastatin liver metabolism and bile excretion might be altered with impaired liver function. Finally, very recent data from a double-blind dose-finding trial conducted in patients with decompensated cirrhosis showed that a dose of 20 mg OD was associated with no muscle toxicity,101 whereas the rate of muscle toxicity with simvastatin 40 mg OD was even higher than in the BLEPS study. This is likely due to the fact that the BLEPS study included patients with less advanced liver disease, and further suggests that patients with decompensated cirrhosis should not be treated with >20 mg OD of simvastatin.…”
Section: Problems With Statin Use In Patients With Advanced Liver Dismentioning
confidence: 97%
“…Several additional steps in simvastatin liver metabolism and bile excretion might be altered with impaired liver function. Finally, very recent data from a double-blind dose-finding trial conducted in patients with decompensated cirrhosis showed that a dose of 20 mg OD was associated with no muscle toxicity,101 whereas the rate of muscle toxicity with simvastatin 40 mg OD was even higher than in the BLEPS study. This is likely due to the fact that the BLEPS study included patients with less advanced liver disease, and further suggests that patients with decompensated cirrhosis should not be treated with >20 mg OD of simvastatin.…”
Section: Problems With Statin Use In Patients With Advanced Liver Dismentioning
confidence: 97%
“…Moreover, considering drug-induced hepatotoxicity as a rare, though well-described side effect of statin as well as increased risk of rhabdomyolysis in patients with chronic liver disease due to impaired CYP3A4 metabolism in the liver, the safety profile of statins in patients with chronic liver disease and liver cirrhosis needs to be evaluated in detail. Thus, just recently Pose et al reported rhabdomyolysis requiring treatment discontinuation in 19% (3/18) of patients with decompensated liver cirrhosis and treatment with 40mg simvastatin per day compared to 14% in 20mg simvastatin or placebo treated patients, respectively [291]. Another study reported severe rhabdomyolysis in 3% of patients with liver cirrhosis and statin use [289].…”
Section: Hepatic Protection Via Lipid-lowering Agentsmentioning
confidence: 99%
“…In another recent clinical trial, addition of simvastatin to the NSBB treatment decreased overall mortality in patients although it failed to reduce the rate of re-bleeding from varices[ 164 ]. Whilst this study showed that 3% of the patients treated with simvastatin developed severe adverse side effects such as rhabdomyolysis, a more recent clinical trial suggested that statins-associated risks appear to be dose-related[ 165 ]. The above clinical evidence suggests that statins possess a clear potential for the treatment of portal hypertension in cirrhotic patients, however, further randomized clinical trials are warranted involving larger patient populations with clear clinical end points.…”
Section: Therapies Targeting Increased Intrahepatic Vascular Tonementioning
confidence: 99%